COMPARATIVE EVALUATION OF THYMOQUINONE AND METHOTREXATE IN LUNG INFLAMMATION IN MURINE MODEL OF RHEUMATIOD ARTHRITIS - Faisal, Rizwan; Imran, Ulfat (Journal of Postgraduate Medical Institute, 2015)
Objective: To determine the effect of thymoquinone and methotrexate onlung in pristine induced inflammation in rats. Methodology: It was a comparative study which was carried out at PostGraduate Medical Institute Lahore. Rats were divided into four equal groupseach consisting of 8 rats (n=8); group A served as healthy control, group B wastaken as positive control, group C was treated with thymoquinone and groupD with methotrexate. Arthritis developed within two weeks after a single pristane injection which is assessed through total leukocyte count. Total leukocyte count was taken at day 0, 15 and 30 while lung tissue for histopathology wastaken at the time of dissection (day 30). Results: The result of this study indicated that development of arthritis was accompanied by significant raise in total leukocyte count and the presence of inflammatory cells in lung histopathological sections as compared to healthy control groups. Both thymoquinone and methotrexate significantly reduced total leukocyte count and number of inflammatory cells as compared to positive control group of arthritic rats. Conclusion: Evaluation of results supported the beneficial effects of both thymoquinone and Methotrexate in lung inflammation produced by murine model of rheumatoid arthritis. Thus thymoquinone can be a potential therapy for rheumatoid lung and needs further evaluation in human models.